Nas trevas: Sonetos sentimentaes e humoristicos - Castelo Branco, Camilo, 1825-1890 (Salt Lake City, UT : Project Gutenberg, 2011)
"Nas trevas: Sonetos sentimentaes e humoristicos" by Camilo Castelo Branco is a collection of sonnets that blend sentimentality and humor, written in the late 19th century. The book reflects on themes of love, loss, and the complexities of human relationships against a backdrop of personal suffering and societal commentary. It showcases the author's poetic prowess while addressing both the melancholic and humorous aspects of life. The collection is divided into two main sections, the first focusing on sentiment and the second incorporating humor. In the sentiment section, Castelo Branco mourns personal losses, expresses deep emotional pain, and explores the nature of existence and human suffering. The humoristic section employs satire to comment on societal issues and political matters, often contrasting the gravity of life with levity. Throughout the sonnets, the poet's introspective voice reveals a deep existential struggle, capturing both the beauty and sorrow inherent in the human experience. The work ultimately serves as both a poignant exploration of individual experience and a reflective critique of society. (This is an automatically generated summary.)
Release date is 2011-01-13
Produced by Pedro Saborano
Keywords: Portuguese poetry -- 19th century; Sonnets